Skywalker: Efficient Alias-Method-Based Graph Sampling and Random Walk on GPUs - Wang, Pengyu; Li, Chao; Wang, Jing; Wang, Taolei; Zhang, Lu; Leng, Jingwen; Chen, Quan; Guo, Minyi (2021 30th International Conference on Parallel Architectures and Compilation Techniques (PACT), 2021)
Graph sampling and random walk operations, capturing the structural properties of graphs, are playing an important role today as we cannot directly adopt computing-intensive algorithms on large-scale graphs. Existing system frameworks for these tasks are not only spatially and temporally inefficient, but many also lead to biased results. This paper presents Skywalker, a high-throughput, quality-preserving random walk and sampling framework based on GPUs. Skywalker makes three key contributions: first, it takes the first step to realize efficient biased sampling with the alias method on a GPU. Second, it introduces well-crafted load-balancing techniques to effectively utilize the massive parallelism of GPUs. Third, it accelerates alias table construction and reduce the GPU memory requirement with efficient memory management scheme. We show that Skywalker greatly outperforms the state-of-the-art CPU-based and GPU-based baselines, in a wide spectrum of workload scenarios.